Pelatihan Pemaknaan dan Pembacaan Ayat-ayat Alquran Untuk Menurunkan Tingkat Stres Mahasiswa yang Sedang Mengerjakan Skripsi - Anshori, Hafiz; Komalasari, Shanty (Faculty of Ushuluddin and Humanities, 2018)
Studentsâ pressures while working on their undergraduate thesis caused psychological impact called stress. The researcher was intended to find out whether any roles of the Quran as a guideline for Muslims reducing the stress level. It is a field research with a quantitative experimental approach which used two groups(pre-test- post-test) design with two variables: training of meaning and reading verses of the Quran (X) and stress level (Y). The subjects were 12 students divided into 6 students in each of experimental and control group. The experimental group used paired samples t-test and got a p-value of 0,035, p <0,05 means there was a difference of scores between pretest and post-test. The control group obtained a p-value of 0.849, p <0.05 means there was no difference in scores between pretest and post-test. Based on the results of different test analysis using independent samples t-test obtained the p-value of 0.000 is smaller than 0.01 showed that there is a significant difference in stress level between the two groups. The results indicate that the training of meaning and reading of Quranic verses can reduce the stress level of students who are working on an undergraduate thesis in the Islamic Psychology Study Program of the State Islamic University of Antasari Banjarmasin.